PERSPEKTIF TOKOH MASYARAKAT DESA SIDOHARJO TANJUNGANOM NGANJUK TENTANG NUSYUZ DAN KEKERASAN DALAM RUMAH TANGGA - Maryam Qurotul Aini, Siti; Lailatul Maghfiroh, Naziyatu (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2022)
Marriage is an inner and outer bond between a man and a woman as husband and wife to form a happy and eternal household (family) based on the Almighty God. But sometimes problems arise in married life, one of which is nusyuz. Nusyuz behavior often occurs in domestic life and has an impact on disharmony. Some of them even lead to acts of domestic violence. This paper presents the perspectives of community leaders in Sidoharjo Village about nusyuz and domestic violence and the relationship between the two. The type of research that will be used is qualitative, namely field research, while the approaches in this research are normative and sociological. Data collection methods used are interviews (interviews), observation, and documentation. Meanwhile, the data validity test was carried out through data triangulation techniques, persistence/consistency of observation, and the use of reference materials to prove the data that had been found. The results of this study indicate that the perspective of Sidoharjo Village community leaders towards nusyuz is when the wife disobeys or disobeys her husband. Then the perspective of community leaders in Sidoharjo Village on domestic violence is violence that occurs in the household. The culprit can be the husband or wife. Furthermore, the perspective of community leaders in Sidoharjo Village on the relationship between nusyuz and domestic violence. They said there was a relationship between the two by explaining that it started with a wife who was rebellious and then the husband could not control his emotions so in the end there was an act of domestic violence.